The annual risk of tuberculosis infection in newly hired researchers and healthcare workers using interferon-gamma release assay in Japan. Issue 8 (August 2020) - Nishimura, Tomoyasu; Ota, Masaki; Mori, Masaaki; Takano, Yaoko; Fujiwara, Hiroshi; Uwamino, Yoshifumi; Uno, Shunsuke; Hasegawa, Naoki
Abstract: The tuberculosis (TB) notification rate in Japan is gradually decreasing but has not yet achieved "pre-elimination, " defined by the World Health Organization. To effectively tackle, control, and eliminate TB, estimating and monitoring the annual risk of TB infection (ARI) using tuberculin skin testing (TST) to understand the dynamics of TB epidemiology are significantly important. However, studies estimating ARIs using TST are few considering that Bacillus Calmette-Guérin vaccination coverage is high in Japan. This was a single-center, cross-sectional study conducted between January 2011 and December 2018 in Tokyo area where interferon-gamma release assays (IGRAs) were performed in newly hired researchers of Keio University School of Medicine and healthcare workers of Keio University Hospital to determine TB infection. We estimated the prevalence of TB infection and ARI based on their IGRA results. Among the 3908 subjects, 83 (2.124%) had positive IGRA results. Multiple logistic regression analysis revealed that age was a significant risk factor for positive IGRA result (adjusted odds ratio, 1.046). The ARIs were 0.049%–0.156% between 1986 and 2004, midyears of TB infection, but have not significantly decreased over approximately two decades. To decrease the risk of TB infection, advanced strategies to control and eliminate TB in Tokyo area are significantly required.